2020
DOI: 10.1039/d0ra04710d
|View full text |Cite
|
Sign up to set email alerts
|

Shortwave-infrared (SWIR) fluorescence molecular imaging using indocyanine green–antibody conjugates for the optical diagnostics of cancerous tumours

Abstract: We present indocyanine green (ICG)-based shortwave-infrared (SWIR) fluorescence molecular imaging for the highly-sensitive optical detection of breast and skin tumours in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…10 Recently, we reported that ICG-annexin V can act as a NIR uorescent dye for cancer cell apoptosis in vitro and in vivo. 22 ICG and ICG-C11 conjugated annexin V (ICG-annexin V and ICG-C11-annexin V) recognize PS on the plasma membrane of apoptotic cells, and they emit SWIR uorescence over 1000 nm (Scheme 1b). Using the annexin V probes, we examined the performance of SWIR uorescence for high-contrast molecular imaging of tumor apoptosis in living mice.…”
Section: Preparation Of Swir Emitting Annexin Vmentioning
confidence: 99%
“…10 Recently, we reported that ICG-annexin V can act as a NIR uorescent dye for cancer cell apoptosis in vitro and in vivo. 22 ICG and ICG-C11 conjugated annexin V (ICG-annexin V and ICG-C11-annexin V) recognize PS on the plasma membrane of apoptotic cells, and they emit SWIR uorescence over 1000 nm (Scheme 1b). Using the annexin V probes, we examined the performance of SWIR uorescence for high-contrast molecular imaging of tumor apoptosis in living mice.…”
Section: Preparation Of Swir Emitting Annexin Vmentioning
confidence: 99%
“…32,38 However, its major limitations include relatively low photon utilization because NIR-II is only the tail portion of the emission spectrum, as well as the nonspecific targeting mechanism of the EPR effect; 39 hence, researchers continue to identify strategies to improve characteristics of NIR-II imaging probes, such as synthesizing organic small molecules with a rapid excretion profile and higher imaging quality compared with free ICG, 40 and conjugating ICG to antibodies targeting overexpressed receptors on cancer cells. 41…”
Section: Icg In the Nir-ii Windowmentioning
confidence: 99%
“…Furthermore, it would have a higher spatial resolution than the sentinel lymph-node biopsy with VIS (Patent blue) or NIR fluorescence (Indocyanine green, ICG) because of the lower scattering property [ 6 , 7 , 8 , 9 ]. Indeed, a fluorescent image of a small breast cancer of several millimeters was obtained from small animal experiments [ 10 ].…”
Section: Introductionmentioning
confidence: 99%